2022
DOI: 10.1177/0308518x221083683
|View full text |Cite
|
Sign up to set email alerts
|

State Capitalism and Spanish port development along the Maritime Silk Road

Abstract: With the rise of ‘new’ state capitalisms, control over transport infrastructure has returned to the forefront of competition in the global economy. This article investigates how different state capitalisms interact to enable economic developments in ports. It tracks the relationship between state-owned firms in the shipping and ports sectors through a case study of the port of Valencia in Spain and COSCO shipping group. The article identifies state capitalisms as variegated and relational to analyze the ways i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…It is worth noticing here that the state capitalism geo‐category has been used to support a ‘new Cold War’ narrative of East‐West competition between two radically different and incompatible models of capitalism (Alami & Dixon, 2020). Nonetheless, research focusing on international ports in Europe, like Valencia in Spain and Piraeus in Greece, has recently shown that Chinese and Spanish as well as Chinese and Greek state capitalist dynamics are synergistically facilitating the creation of competitive, new logistics infrastructures in Europe (Apostolopoulou, 2021b; Jensen, 2022).…”
Section: Bri As Project: State Market and Geopolitical Economymentioning
confidence: 99%
“…It is worth noticing here that the state capitalism geo‐category has been used to support a ‘new Cold War’ narrative of East‐West competition between two radically different and incompatible models of capitalism (Alami & Dixon, 2020). Nonetheless, research focusing on international ports in Europe, like Valencia in Spain and Piraeus in Greece, has recently shown that Chinese and Spanish as well as Chinese and Greek state capitalist dynamics are synergistically facilitating the creation of competitive, new logistics infrastructures in Europe (Apostolopoulou, 2021b; Jensen, 2022).…”
Section: Bri As Project: State Market and Geopolitical Economymentioning
confidence: 99%
“…While Chinese state-owned shipping enterprises and Spanish port authorities have varied political-economic strategies, these have not been mutually exclusive or incompatible. Synergies between the two increasingly shape port development and macro-regional logistical networks in Europe, in the context of acute competitive pressures from global shipping markets (Jensen, 2023). Kinossian and Morgan's (2023) analysis of two state-sponsored megaprojects in Russiathe upgrade of the Northern Sea Route and the construction the of Skolkovo Innovation Centreuncovers their role in the reproduction of an authoritarian form of state capitalism.…”
Section: Introductionmentioning
confidence: 99%
“…The six articles featured in this second installment of the theme issue all advance the plenary claim that geography matters to the study of present-day state capitalism. In ‘State Capitalism and Spanish port development along the Maritime Silk Road’, Jensen (2023) studies the dynamic interactions between Spanish and Chinese state-capitalist trajectories and their material expression in maritime transport infrastructure, based on a case study of the port of Valencia in Spain and Chinese state-owned COSCO shipping group. While Chinese state-owned shipping enterprises and Spanish port authorities have varied political-economic strategies, these have not been mutually exclusive or incompatible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The papers of the theme issue equally highlight the temporal attributes of the new state capitalism by offering distinctive case-study periodizations, each with their own time frames (Palcic et al, 2023; Silverwood and Berry, 2023), by emphasizing extraterritorial dimensions (Jensen, 2023; McGregor and Coe, 2023) and by making connections with neoliberalization (Paul and Cumbers, 2023) and financialization (Petry et al, 2023; Ward et al, 2023). Rather than taking the ‘new’ state capitalism moniker for granted, the concept of novelty itself is also critically assessed (e.g., Alami and Dixon, 2023 on global capitalism; Eagleton-Pierce, 2023 on temporal fluidity; Su and Lim, 2023 on China).…”
mentioning
confidence: 99%